Evaluation in situ of genotoxicity and stress in South American common toad Rhinella arenarum in environments related to fluorite mine - Pollo, Favio Ezequiel (2017)
Little attention has been paid to the impact of wastewater generated by mining activities on fluoride. In this study, we evaluated the hematology responses of common South American toad Rhinella arenarum inhabiting natural and artificial environments associated with a fluorite mine from central Argentina. We analyzed three sampling stations associated with the fluorite mine: (I) Los Cerros Negros stream (CN), which runs on granitic rock with a high fluorite content; (II) Los Vallecitos stream (LV), which runs on metamorphic rock with low fluorite content; and (III) artificial decantation ponds (DP) containing sediments produced by fluorite flotation process. We calculated frequencies of micronuclei, erythrocyte nuclear abnormalities, mitosis, and immature erythrocytes. In addition, we performed a differential leukocyte count and determined neutrophils/lymphocyte ratio as a stress response estimator. We found high micronucleus (MN) and erythrocyte nuclear abnormality (ENA) frequencies in DP and CN but low frequencies in LV. The neutrophil/lymphocyte ratio was different among sites, with a significant increase in individuals from DP. Values registered in DP could be caused by exposure to mixture of compounds registered in dams that hold wastewater, while high values registered in CN stream might be due to natural concentrations of fluoride. Our results suggest that blood is an effective and non-destructive sensitive indicator for monitoring genotoxic agents in freshwater ecosystems.